Telerehabilitation for people with low vision - Bittner, Ava K (Cochrane Database Syst Rev, 2015)
BACKGROUND: Low vision affects over 300 million people worldwide and can compromise both activities of daily living and quality of life. Rehabilitative training and vision assistive equipment (VAE) may help, but some visually impaired people have limited resources to attend in-person visits at rehabilitation clinics. These people may be able to overcome barriers to care through remote, Internet-based consultation (i.e., telerehabilitation). OBJECTIVES: To compare the effects of telerehabilitation with face-to-face (e.g., in-office or inpatient) vision rehabilitation services for improving vision-related quality of life and reading speed in people with visual function loss due to any ocular condition. Secondary objectives are to evaluate compliance with scheduled rehabilitation sessions, abandonment rates for visual assistive equipment devices, and patient satisfaction ratings. SEARCH METHODS: We searched CENTRAL (which contains the Cochrane Eyes and Vision Group Trials Register) (2015 Issue 5), Ovid MEDLINE, Ovid MEDLINE In-Process and Other Non-Indexed Citations, Ovid MEDLINE Daily, Ovid OLDMEDLINE (January 1980 to June 2015), EMBASE (January 1980 to June 2015), PubMed (1980 to June 2015), ClinicalTrials.gov (www.clinicaltrials.gov) and the World Health Organization (WHO) International Clinical Trials Registry Platform (ICTRP) (www.who.int/ictrp/search/en). We did not use any language restriction or study design filter in the electronic searches; however, we restricted the searches from 1980 onwards because the Internet was not introduced to the public until 1982. We last searched the electronic databases on 15 June 2015. SELECTION CRITERIA: We planned to include randomized controlled trials (RCTs) or controlled clinical trials (CCTs) in which participants were diagnosed with low vision and were undergoing low vision rehabilitation using an Internet, web-based technology compared with an approach based on in-person consultations. DATA COLLECTION AND ANALYSIS: Two authors independently screened titles and abstracts, and then full-text articles against the eligibility criteria. We planned to have two authors independently abstract data from included studies. We resolved discrepancies by discussion. MAIN RESULTS: We did not find any study that met the inclusion criteria for this review and, hence, we did not conduct a quantitative analysis. As a part of the background, we discussed review articles on telemedicine for facilitating communication with elderly individuals or for providing remote ophthalmological care. AUTHORS’ CONCLUSIONS: We did not find any evidence on whether the use of telerehabilitation is feasible or a potentially viable means to remotely deliver rehabilitation services to individuals with low vision. Given the disease burden and the growing interest in telemedicine, there is a need for future pilot studies and subsequent clinical trials to explore the potential for telerehabilitation as a platform for providing services to people with low vision.